Study of sand fly fauna in an endemic area of American cutaneous leishmaniasis and canine visceral leishmaniasis in the municipality of Espírito Santo do Pinhal, São Paulo, Brazil - Fernanda Elisa Colla-Jacques; Cláudio Casanova; Ângelo Pires do Prado (Memorias do Instituto Oswaldo Cruz, 2010)
Canine American visceral leishmaniasis and American cutaneous leishmaniasis (ACL) cases have been recorded in Espírito Santo do Pinhal. The aim of this study was to gather knowledge of the sand fly community and its population ecology within the municipality. Captures were made weekly over a period of 15 months in the urban, periurban and rural areas of the municipality, using automatic light traps. A total of 5,562 sand flies were collected, comprising 17 species. The most abundant species were Nyssomyia whitmani and Pintomyia pessoai in the rural area, Lutzomyia longipalpis and Ny. whitmani in the periurban area and Lu. longipalpis in the urban area. The highest species richness and greatest index species diversity were found in the rural area. The similarity index showed that urban and periurban areas were most alike. Lu. longipalpis was found in great numbers during both dry and humid periods. The presence of dogs infected with Leishmania infantum chagasi in the urban area indicates a high risk for the establishment of the disease in the region. A high abundance of Ny. whitmani and Pi. pessoai in the rural and periurban areas indicates the possibility of new cases of ACL occurring in and spreading to the periurban area of Espírito Santo do Pinhal.